Ultrasonographic demonstration of the superior ophthalmic vein in the orbit of premature infants with and without retinopathy of prematurity. Issue 5 (November 2015) - Ron, Yonina; Barash, David; Erhenberg, Miriam; Friling, Ronit; Osovsky, Micky; Sirota, Lea; Snir, Moshe; Ehrlich, Rita
Abstract Retinopathy of prematurity (ROP), which develops due to abnormal retinal vascularization in premature babies, can lead to irreversible vision loss. B-scan ocular ultrasonography is a noninvasive examination which makes it possible to image the eye and orbit. Our purpose was to echographically assess the orbit of premature babies with and without retinopathy of prematurity (ROP), with a focus on the superior ophthalmic vein (SOV) which is normally not detected by orbital ultrasound. A prospective study design was used after approved by the local institutional review board. ROP was diagnosed by routine ophthalmoscopic exam. Orbital ultrasound was performed by a single experienced ophthalmologist and ultra-sonographer who was masked to the routine ROP screening results. The results of the ophthalmoscopic exam were compared to the orbital ultrasound findings. The study group was divided into those diagnosed with ROP and those not diagnosed with ROP and were found to be comparable by age and weight at the time of the US examination. The SOV was dilated in 21 of 22 eyes (95.4%) with ROP and in only 5 of 32 eyes (15.6%) without ROP. The present study suggests an association between ROP and dilatation of the SOV.